Hierarchy, revisionism, and subordinate actors: The TPNW and the subversion of the nuclear order. (December 2022) - Egel, Naomi; Ward, Steven
Why and how do weak states challenge the status quo? This article builds on analyses of hierarchy in International Relations to develop a more comprehensive and inclusive understanding of the concept of revisionism. We argue that while weak actors cannot generally directly challenge their position in a stratified hierarchy, they may be able to undermine or subvert the discourses that constitute these hierarchies. This approach is likely to be attractive and feasible under two conditions: when other approaches to reform have been frustrated, and when social and political resources are available to facilitate such subversive challenges. We illustrate this argument by analyzing the Treaty on the Prohibition of Nuclear Weapons as a subversive revisionist project. Small states—frustrated by their inability to negotiate meaningful reform through the status quo framework—partnered with civil society and drew upon discursive resources developed during prior subversive revisionist projects in an effort to stigmatize nuclear weapons and subvert the discourses constituting the advantaged positions of those possessing them. While the Treaty on the Prohibition of Nuclear Weapons (TPNW) is unlikely to directly persuade nuclear weapon states to abandon their arsenals, it could have unpredictable consequences across a related range of hierarchic fields that constitute the status quo order.